'Peptide receptor radionuclide therapy in the management of advanced pheochromocytoma and paraganglioma: A systematic review and meta‐analysis'. (13th October 2019) - Satapathy, Swayamjeet; Mittal, Bhagwant Rai; Bhansali, Anil
Abstract: Objective: Inoperable and metastatic pheochromocytomas and paragangliomas (PPGLs) present a therapeutic challenge with current treatment options being limited to radiolabelled meta‐iodo‐benzyl‐guanidine (MIBG) and systemic chemotherapy. Peptide receptor radionuclide therapy (PRRT) seems to be a promising option for these patients with few studies reporting favourable response. This systematic review was conducted to evaluate the efficacy and safety of PRRT in patients with advanced PPGLs. Methods: This review followed the Preferred Reporting Items for Systematic Reviews and Meta‐Analysis (PRISMA) guidelines. Searches in PubMed, Scopus and Embase were made using relevant keywords and articles up to May 2019 were included. Data on efficacy and toxicity were extracted from the individual articles, and pooled estimates were generated using meta‐analysis. Results: Twelve articles consisting of 201 patients with advanced PPGLs were included. Overall, treatment with PRRT achieved an objective response rate of 25% (95% CI: 19%‐32%) and a disease control rate of 84% (95% CI: 77%‐89%). Clinical and biochemical responses were seen in 61% and 64% of the patients, respectively. Among the PRRTs, similar tumour response rates were noted for 90 Y—yttrium‐ and 177 Lu—lutetium‐based agents. Treatment‐related adverse effects were minimal with grade 3/4 neutropenia, thrombocytopenia, lymphopenia and nephrotoxicity observed in 3%, 9%, 11% and 4% of the patients, respectively. Treatment discontinuation was noted in five out of 102 patients. Conclusions: Peptide receptor radionuclide therapy is a safe and efficacious treatment option for advanced PPGLs and may be considered a viable alternative to chemotherapy and I‐ 131 MIBG.